Highly luminescent gold nanoparticles: effect of ruthenium distance for nanoprobes with enhanced lifetimes. (30th September 2015) - Osborne, Shani A. M.; Pikramenou, Zoe
Abstract : The photophysical properties of gold nanoparticles, AuNPs, with sizes of 13, 50 and 100 nm in diameter, coated with surface-active ruthenium complexes have been studied to investigate the effect of the distance of the ruthenium luminescent centre from the gold surface. Luminescence lifetimes of the three ruthenium probes, RuS1, RuS6 andRuS12, with different length spacer units between the surface active groups and the ruthenium centre were taken. The metal complexes were attached toAuNP13, AuNP50 andAuNP100 via thiol groups using a method of precoating the nanoparticles with a fluorinated surfactant. The luminescence lifetime of the longer spacer unit complex, RuS12, was enhanced by 70% upon attachment to the AuNP when compared to the increase of the short and medium linker unit complexes, RuS1 (20%) andRuS6 (40%) respectively. The effect of the surfactant in the lifetime increase of the ruthenium coated AuNPs was shown to be larger for the medium spacer probe, RuS6 . There was no effect of the change of the size of the AuNPs from 13 to 50 or 100 nm.